Electrical bio-sensing based on non-antibody recognition elements - Chen, Hu (2017)
This study focuses on monitoring of sports fatigue related biomarkers using electrical assays (i.e., field-effect transistor sensing and tunable resistive pulse sensing) that are based on non-antibody recognition elements. The main hypothesis is that assays based on synthetic receptors can deliver sensing performances comparable to that of conventional antibody based ones, while providing advantages such as excellent stability in harsh environments, facile synthesis process, and small molecular sizes. Three specific hypotheses have been proposed. First, it is proposed that sports fatigue related biomarkers can be measured quantitatively in real time using carbon nanomaterial based FET sensors. Second, it is proposed that synthetic receptors such as liposomes and polypeptides can be used in combination with carbon nanomaterial based FET sensors for the monitoring of sports fatigue related biomarkers. Third, it is proposed that aptamers can be used in combination with tunable resistive pulse sensing for bio-sensing applications.